DEVELOPMENT OF E-MODULES BASED ON PROJECT BASED LEARNING (PjBL) TO INCREASE STUDENT’S INTEREST IN LEARNING AND LEARNING OUTCOMES ON REACTION RATE MATERIAL - Siregar, Nurhidayah; Syafriani, Dewi (UNDIKMA, 2024)
This research aims to: (1) determine the validity of e-modules based on project based learning, (2) determine the practicality of e-modules based on project based learning, (3) determine the effectiveness of e-modules based on project based learning, and (4) determine whether there is a significant correlation between interest and learning outcomes. This research was conducted at SMA Negeri 10 Medan with the sample studied was class XI IPA 2. The data analysis technique is carried out by: e-module feasibility test according to BSNP, learning interest test, and correlation test between learning interest and learning outcomes. The results obtained in this research are: (1) E-modules based on project based learning are considered